+0

0
46
2
+32

2x+13x +15=0 (2x +___)(x+___)

yahya  Sep 8, 2017
edited by yahya  Sep 8, 2017
Sort:

#1
+18564
+2

2x2 +13x +15=0

(2x +___)(x+___) = 0

$$\begin{array}{|lrcll|} \hline (2x + a)(x+ b) &=& 0 \\ 2x^2 + 2xb+ax+ab &=& 0 \\ 2x^2 + x\underbrace{(a+2b)}_{=13} + \underbrace{ab}_{=15} &=& 0 \quad |& \quad \text{compare with } 2x^2 +13x +15=0 \\\\ (1) & ab &=& 15 \\ & b &=& \frac{15}{a} \\\\ (2) & a+2b &=& 13 \\ & a + \frac{2\cdot 15}{a} \\ & a + \frac{30}{a} &=& 13 \quad | \quad \cdot a \\ & a^2 + 30 &=& 13a \\ & a^2 -13a + 30 &=& 0 \\\\ & (a-10)(a-3) &=& 0 \\\\ & \mathbf{a_1 = 10} & \text{and} & \mathbf{a_2 = 3} \\\\ & b_1 = \frac{15}{10 } && b_2 = \frac{15}{3} \\ & \mathbf{b_1 = 1.5} && \mathbf{ b_2 = 5} \\ \hline \end{array}$$

$$\begin{array}{|rcll|} \hline (2x + 10)(x+1.5) = 0 \\ \text{ or } \\ (2x + 3)(x+ 5 ) = 0 \\ \hline \end{array}$$

heureka  Sep 8, 2017
#2
+6915
+2

2x2 +13x +15=0  (2x+   )(x+   )

$$2x^2 +13x +15=0$$

a           b            c

$$x = {-b \pm \sqrt{b^2-4ac} \over 2a}$$

$$x = {-13 \pm \sqrt{169-4\cdot 2\cdot 15} \over 2\cdot 2}$$

$$x=\frac{-13\pm\sqrt{49}}{4}$$

$$x_1=-\frac{3}{2}\\ x_2=-5$$

$$(x+5)(x+\frac{3}{2})=x^2+\frac{3}{2}x+5x+\frac{15}{2}\\ (x+5)(x+\frac{3}{2})=x^2+\frac{13}{2}x+\frac{15}{2}$$

$$2(x+5)(x+\frac{3}{2})=2x^2 +13x +15$$

$$(x+5)(2x+3)=2x^2 +13x +15$$

!



asinus  Sep 8, 2017
edited by asinus  Sep 8, 2017

### 17 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details